A Non-Invertible Secure Template Generation Using AES Encrypted MCC and Random Triangle Projection - Mohd Imran; Mohammad Sarosh Umar; Furkan Ahmad (IEEE Access)
In recent years, due to the exponential growth in the applicability of biometric authentication systems, it has become essential to address the privacy and security concerns of user biometric information. The cancellable biometric template generation is one of the promising solutions in this situation which protects both the system and the user’s biometric data from unauthorized access. The complexity of such a system which sustains improved performance while maintaining the anonymity of users by introducing non-invertibility, unlinkability, and encapsulation of encrypted templates is a difficult task. The random projection-based cancellable biometric template generation is one of the efficient techniques to secure the information of users. But still, this approach suffers from the adversary attack where an attacker can obtain the original template by performing repeated random projections on the stored template. In this paper, we proposed a technique: MCC Encoded Random Triangle Hashing which protects the biometric template by encoding the projection matrix with the minutiae cylindrical codes obtained from the minutiae information. This technique addresses the problem where the projection matrix is leaked to an attacker which can lead to the reconstruction of the original biometric template. The performance of the proposed technique is evaluated using FMR, FAR, GAR, ROC Curve, and EER parameters on six FVC fingerprint databases FVC2000 DB1, FVC2000 DB2, FVC2002 DB1, FVC2002 DB3, FVC2004 DB1, and FVC2004 DB3 which is publicly available.